2016
DOI: 10.1007/s11096-016-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with regulatory resolutions on prevention of NSAIDs-related gastrointestinal injury in Italy

Abstract: Background The rate of gastrointestinal (GI) complications with non-steroidal antiinflammatory drugs (NSAIDs) or low-dose aspirin (LD-ASA) varies according to risk factors. For at risk patients, the Italian regulatory resolution enforce prophylaxis with proton pump inhibitors (PPIs) or misoprostol. Objective This study evaluated the consistency with such resolution in patients receiving NSAIDs or LD-ASA and assessed whether patients continued to receive GI protection with PPIs for an adequate time following NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…Preventable cases were detected in all age groups, including infants, adolescents, and elder. This result was expected considering that previous studies have evidenced a widespread inappropriate use of NSAIDs involving both young and elder users in the Italian population (Motola et al, 2004; Scarpignato et al, 2015; Cardile et al, 2016; Montagnani et al, 2016). Moreover, this result is in line with the drug utilization data published by AIFA which evidenced a higher use of preventive measure for gastrolesivity among patients with an age greater or equal to 65 years old that were concurrently exposed to multiple gastrolesive drugs (The Medicines Utilisation Monitoring Centre., 2015).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Preventable cases were detected in all age groups, including infants, adolescents, and elder. This result was expected considering that previous studies have evidenced a widespread inappropriate use of NSAIDs involving both young and elder users in the Italian population (Motola et al, 2004; Scarpignato et al, 2015; Cardile et al, 2016; Montagnani et al, 2016). Moreover, this result is in line with the drug utilization data published by AIFA which evidenced a higher use of preventive measure for gastrolesivity among patients with an age greater or equal to 65 years old that were concurrently exposed to multiple gastrolesive drugs (The Medicines Utilisation Monitoring Centre., 2015).…”
Section: Discussionsupporting
confidence: 56%
“…As the result of initiatives to improve the identification of medication errors in the individual case safety reports (ICSRs) promoted by World Health Organization (Pal et al, 2015), and recently strengthen in Europe (European Medicine Agency, 2011, 2013), committees were introduced in Italy to meet these new regulatory tasks (Bencheikh and Benabdallah, 2009; Sessa et al, 2016a,d). Although on the Italian national territory evidence was provided regarding the association between inappropriate use of NSAIDs and the risk of experiencing serious and non-serious ADRs (Montagnani et al, 2016; Rafaniello et al, 2016), no studies were conducted to assess the magnitude of their preventability, highlighting the need of gain further insight on this aspect. This is even more important considering that on the National territory, several NSAIDs were sold as over-the-counter medications, which dispensing profile is well known to lead to abuse in their usage, with harms being increasingly recognized (Cooper, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the most common inappropriate use of PPI is for the prevention of gastric damage in co-therapy with agents that have a low gastrotoxicity, if any, or in patients without GI risk factors for significant gastroduodenal damage [30, 31, 425427] as well as in the prevention of stress-induced bleeding [14, 428430]. PPIs are often started as an inpatient treatment and continued (often long-term) on discharge for non-indicated reasons [14, 431, 432].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, despite all guidelines supporting the use of gastroprotection with PPIs in at-risk patients treated with NSAIDs [2628], low prescription rates of gastroprotective medications have been reported, although these rates have increased progressively (for review see [28]). In Italy, three studies [2931] reported a substantial misuse of gastroprotection in primary care. In particular, an underuse rate of 25 − 30 % or an overuse (young patients without any concomitant risk factor) as high as 57.5 % were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo europeu mostra que os IBPs continuam sendo prescritos fora das diretrizes de tra-tamento, como prevenção de dano gástrico e hemorragias gástricas decorrentes ocasionadas pelo estresse. Outro motivo é a utilização para pacientes internados que após alta hospitalar continuam com o tratamento, muitas vezes a longo prazo, por razões não indicadas 15,16,17,18 . Thomas e colaboradores avaliaram prescrições de mais de 20.000 pacientes que receberam IBPs de forma inadequada após a internação hospitalar ao longo de um período de 4 anos com custo de aproximadamente 3.000.000 de dólares 19 .…”
Section: Discussionunclassified